PENGARUH SALURAN PENJUALAN DAN STRATEGI PEMASARAN TERHADAP PENJUALAN PADA ROTI PAKCIK TANJUNG MORAWA - Yudistira Bagas Pratama; Mustika Dewi; Aulia Akbar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid growth of the food industry, particularly within the bakery sector, requires business actors to develop well-structured strategies in order to remain competitive in an increasingly demanding market. This study was prompted by the pronounced sales fluctuations observed at Roti Pakcik Tanjung Morawa throughout 2025, which are presumed to stem from suboptimal management of sales channels and marketing strategies. This research was conducted to examine how sales channels and marketing strategies affect sales performance, both individually and in combination. The study adopted a quantitative approach based on a causal associative design. A sample of 97 respondents was determined using the Lemeshow formula, with data gathered through three methods: direct observation, interviews, and questionnaires.